Imagery Techniques in Modern Jewish Mysticism - Reiser, Daniel, 1976- (De Gruyter, 2018)
"This book analyzes and describes the development and aspects of imagery techniques, a primary mode of mystical experience, in Jewish mysticism. Imagery techniques of twentieth century Jewish mysticism, in contrast to linguistic imagery techniques in medieval Kabbalah, are comparable to screenplays or feature films. This development can be fruitfully contextualized within broader trends of Western and Eastern imagery techniques"-- Provided by publisher
Keywords: Imagery (Psychology) -- Methodology -- History -- 20th century.; Imagination (Philosophy) -- History -- 20th century.; Visualization -- Technique -- History -- 20th century.; Mysticism -- Judaism -- History -- 20th century.; Imagerie (Psychologie) -- Méthodologie -- Histoire -- 20e siècle.; Visualisation -- Technique -- Histoire -- 20e siècle.; Mysticisme -- Judaïsme -- Histoire -- 20e siècle.; PSYCHOLOGY -- Cognitive Psychology.; SCIENCE -- Cognitive Science.; Imagination (Philosophy); Mysticism -- Judaism; Visualization -- Technique; 1900-1999; History